ENHANCING ORGANIZATIONAL CITIZENSHIP BEHAVIOUR THROUGH MEANINGFUL WORK: EVIDENCE FROM COMMERCIAL BANKS IN LAFIA, NASARAWA STATE - Ayorinde, Oluwafemi Ebenezer; Azizi, Stephen Akolome; Anshir, Stephen Simon (African Journal of Social and Behavioural Sciences, 2025)
In the current competitive world, all organisations look at different ways to stay tuned in the marketplace and continuously explore various means to perform optimally. Consequently, organizational researchers and professionals in the sector have started dedicating attention and resources to understanding the antecedents of Organizational Citizenship Behaviour (OCB). This study is, therefore, one of those research efforts targeted at understanding the antecedents of OCB in the workplace by investigating the influence of Meaningfulness of work on organisational citizenship behaviour among employees of commercial banks in Lafia, Nasarawa State. A cross-sectional research approach was used, and a total of 250 comprising 143 (57.2%) males and 107 (42.8%) females within the age range of 23 – 56 years and a mean age of 36.34(SD=8.44) respondents were purposively selected for the study. Work as Meaning Inventory (WAMI) and Organizational Citizenship Behaviour Checklist (OCB-C) were used to assess participants’ meaningfulness of work and organizational citizenship behaviour, respectively. Results showed a significant positive prediction of meaningfulness of work [R =.441, R2=.195, F (3,346) =19.823; p<.01] among employees of commercial banks in Lafia. The implications of these findings for the banking sector were discussed. It was recommended, among other things, that Organizations should focus on and align their policies to create and maintain conditions responsible for nurturing OCB among their employee.